Melampaui Ekoteologi Normatif: Merespons Ekstraktivisme melalui Gerakan Lingkungan Nahdlatul Ulama dan Muhammadiyah - Mim Maulana Mubarok; Amir Maliki Abitolkha; Muhammad Yusuf Marjani (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT Indonesia’s ecological crisis is exacerbated by extractive economic models that degrade natural resources. As the two largest Islamic organizations, Nahdlatul Ulama and Muhammadiyah possess strategic moral legitimacy to respond to this crisis. This study analyzes the eco-theological orientation of Nahdlatul Ulama and Muhammadiyah and identifies the gap between normative narratives and structural change. Employing a qualitative approach, this research uses literature review and document analysis of fatwas, congress decisions, and environmental programs from 2010-2024. The findings show that the eco-theological orientation of both organizations remains predominantly normative-communitarian, focusing on moral education, ecological da’wah, and local micro-actions. While effective in raising awareness, this approach has not addressed the root causes related to macro political-economic policies and unequal resource governance. To bridge this gap, this article proposes the concept of “structural eco-theology” as an alternative framework. Structural eco-theology integrates Islamic theological foundations with public policy advocacy, cross-sector coalitions, and corporate accountability mechanisms. This framework directs religious moral legitimacy to promote regulatory reform and natural resource governance toward systematic and sustainable ecological justice. Keywords : Structural eco-theology, extractivism, Nahdlatul Ulama, Muhammadiyah, public policy